Corvée Labour and the Habitant “Spirit of Mutiny” in New France, 1688–1731 - Tomczak, Richard H. (Labour / Le Travail, 2021)
The article examines the evolution of Canadian corvée labour in the late 17th- and early 18th-century French Empire. In New France, tenants, referred to as habitants, rented land from seigneurs in exchange for several taxes. The labour tax, or corvée, required habitants to work on their seigneur’s estate for one to two days a year. Additionally, habitants were responsible for providing corvée for building any public infrastructure that the community required. From the Nine Years’ War (starting in 1688) to the construction of the Chemin du Roy (1732), colonial officials experimented with mass corvée labour mobilization in Canada. A number of factors allowed habitants to challenge authority when they felt the colonial élite had violated their right to subsistence. When drafted annually into forced labour for the construction of Québec and Montréal’s fortifications, groups of habitants refused to show up for work, called upon their superiors to protect them from service, or collectively discussed mutiny if conditions did not improve. During the first three decades of the 18th century, corvée was a negotiated process, with habitants constantly putting forth their own definitions of acceptable labour mobilization.